Possibilities of developing novel potent antitumor agents from the leaves of Cryptomaria japonica - Laxmi Rani Basu; Amiyangshu De; Amiyangshu De; Pradipta Sarkar; Prithviraj Karak; Sujata G Dastidar (International Journal of Phytomedicine, 2016)
During past few decades cancer has remained as the largest cause of mortality worldwide and number of patients suffering from cancer has been increasing at a fast rate. Hence medical research during the last few decades has been concentrating on identification and characterization of new synthetic pharmacological compounds to overcome this enormous problem. Leaf extracts of coniferous plant Cryptomeria japonica being known for their strong antibacterial and antifungal functions were selected to determine their antitumor/anticancer potentialities. Methanolic extract of leaves were tested to determine its antitumor action in standard murine model of Ehrlich Ascites Carcinoma (EAC). Graded doses of the extract were given intraperitoneally to batches of mice, who received EAC challenge after 3hr. Treatment with same amounts of extract was continued for 9 consecutive days. Protective capacity of the leaf extract was evaluated in animals. Statistically significant protection was observed with respect to different parameters including tumor volume , tumor cell count , viable tumor cell count, non- viable tumor cell count , mean survival time and increase in life span. Simultaneously hematological parameters were restored in treated mice vis-à-vis untreated control animals. Furthermore, the extract revealed distinct cytotoxic property, which may be the relevant reason of its anticancer/antitumor function. This study shows efficacy of methanolic extract of leaves of Cryptomeria japonica as a probable antitumor/anticancer agent. Phytochemical analysis of the extract showed presence of flavonoids, which are known to possess significant anticancer activity. Thus there is a definite possibility of developing novel anticancer drugs from such plant products